2022
DOI: 10.1007/s00330-022-09032-7
|View full text |Cite
|
Sign up to set email alerts
|

AI-assisted biparametric MRI surveillance of prostate cancer: feasibility study

Abstract: Objectives To evaluate the feasibility of automatic longitudinal analysis of consecutive biparametric MRI (bpMRI) scans to detect clinically significant (cs) prostate cancer (PCa). Methods This retrospective study included a multi-center dataset of 1513 patients who underwent bpMRI (T2 + DWI) between 2014 and 2020, of whom 73 patients underwent at least two consecutive bpMRI scans and repeat biopsies. A deep learning PCa detection model was developed to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
(29 reference statements)
1
6
0
Order By: Relevance
“…Delta radiomics from serial MRI in conjunction with routine clinical parameters (including PSA and tumor volume) may be used to non-invasively predict pathologic progression in PCa patients on AS. Our findings align with those from previous studies ( 36 , 41 , 48 ), which suggest that machine learning and deep learning approaches with prostate MRI can enable non-invasive monitoring of patients on AS. Future directions will involve large-scale multisite validation of delta radiomics approaches from serial MRI, automated and reliable pipelines for lesion detection, and prospectively validating these approaches in a clinical setting.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Delta radiomics from serial MRI in conjunction with routine clinical parameters (including PSA and tumor volume) may be used to non-invasively predict pathologic progression in PCa patients on AS. Our findings align with those from previous studies ( 36 , 41 , 48 ), which suggest that machine learning and deep learning approaches with prostate MRI can enable non-invasive monitoring of patients on AS. Future directions will involve large-scale multisite validation of delta radiomics approaches from serial MRI, automated and reliable pipelines for lesion detection, and prospectively validating these approaches in a clinical setting.…”
Section: Discussionsupporting
confidence: 91%
“…Another related study was the one by Roest et al. who developed a deep learning model using serial MRI for monitoring PCa progression ( 41 ). They built a U-Net-based deep learning model to detect clinically significant prostate cancer (csPCa) at baseline and follow-up MRI, and extract differential tumor volume and csPCa likelihood scores, which were then used to train a supervised machine learning model to detect csPCa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, in the systematic review prepared by Sushentsev et al [54], the authors present a comparable performance of fully automated and AI-assisted techniques. However, in the review by Roest et al [55], the automated system meets the performance of expert radiologists with lower sensitivity. Implementing AI models markedly increased the accuracy of prostate image interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, research into prostate cancer has demonstrated promising performances of ML models in detecting prostate cancer on MRI scans. Their best performing models achieved area under the curve (AUC) rates between 0.78 and 0.87 [38][39][40][41], surpassing the diagnostic performance of radiologists in one paper (AUC 0.81 vs. 0.69, p = 0.02) [39] and enhancing the specificity of PI-RADS assessment by senior radiologists in another (from 52.5% to 72.6%) [40].…”
Section: Discussionmentioning
confidence: 99%